Histomorphological And Histochemical Studies On Embryonic Differentiation Of Goat Caecum (Applied Biological Research, 2017)
The present study was conducted on caecum of twenty one goat fetuses (n = 21)  of different gestation periods. The mucosal projections appeared in caecum  during early stages of development at 45 days (W =3 g) while as villi were first  observed at 78 days (w = 100 g). The degeneration of villi started at 107 days (W = 400 g) and villi disappeared at 130 days (W = 900 g). The epithelium was  undifferentiated stratified-type during early development and started  transforming to simple columnar at 107 days (W = 400 g). The goblet cells  appeared in caecum at 91 days (W = 200 g). The intestinal glands were fully  differentiated in caecum at 120 days (W = 650 g). The lamina muscularis  mucosae appeared in caecum at 130 days (W = 900 g). Tunica muscularis comprised of inner circular and outer longitudinal layer in full term fetus.  Tunica serosa was well organized at full term. The varying amounts of muco polysacchagoatrides, total lipids, and phospholipids were localized.
Keywords: Caecum; goat; histomorphology; histochemistry; prenatal